ANALISIS KELANGKAAN BAHAN BAKAR MINYAK PREMIUM DI STASIUN PENGISIAN BAHAN BAKAR UMUM (SPBU) KABUPATEN KARIMUN TAHUN 2013-2014 - Harahap, Nelpan Gustian; ", Ishak (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
PT. Ology Karimun Bumi Sukses are subsidiaries of the Company Karimun regency has the right to manage the General Fuel Filling Stations in Karimun. because PT. Ology Karimun Bumi Sukses Has a 51% stake, while the regional government only has 49%. In the Year 2013-2014 General Fuel Filling Stations in Karimun experienced shortages.This study aimed to describe or explain how the mechanism of distribution of fuel oil in the General Fuel Filling Station Karimun and the factors that influence on the scarcity of fuel oil (Premium) is. As well as any efforts made by the Government in addressing the scarcity happened.From the research results can be found constraints or factors inhibiting the mechanism of distribution of fuel oil as a constraint to bad weather, quotas limited mileage far enough and the behavior of traders who hoard fuel oil being filled back and forth in the Station General Fuel Filling. So also with the regional government, many of the policies issued from purchase restrictions, placing the security forces in General Fuel Filling Stations up to hold one more unit of the General Fuel Filling Stations are new.Keywords: Scarcity, Distribution Mechanism